Hegemonic Party System and Federalism - Yohannes Haile Getahun (African Journal of Political Science)
The paper inquiries into the fixture of the hegemonic Ethiopian Peoples’ Revolutionary Democratic Party (EPRDF) in the operation of the Ethiopian federal constitutional order. It finds out the federal malfunction of EPRDF. The hegemonic political program of the front, which took the shape of a non-competitive dominant party was not in line with the constitutional diversity of the federal system, as it delinked the constitutional right to self-determination and federal autonomy from the options of multiparty politics. On the structure of EPRDF, equal representation was favorable to the federal politics of diversity accommodation and minority protection. However, the exclusiveness of its structure from the “affiliate” parties had the effects of a narrow-based federal shared-rule, as EPRDF which was the only channel to influence the center. Party-state inseparability was the other gap to the check of power and in establishing the neutrality of the state to deal with ethnic-driven conflict, as a major pathology to the stability of ethnic federal systems. Finally, the power nucleus in the EPRDF created the dominance of TPLF at the perils of diminishing the representative legitimacy and the subordinate position of the “affiliate parties” to EPRDF.